Integrated Low Voltage DC Link for Remote Households using Photovoltaic Cells - Anita Maria Sunny, Arjay J, Mohammed Ali Sajid, Nabeel Mohammed, Baiju R. Naina (International Journal of Advanced Science and Technology, 2020)
The intended purpose of this paper is to deploy an integrated system  incorporating a low voltage direct current system within buildings to serve as support system for low power load demands like LED lights, BLDC fans, desktops computers etc along with a backup source for loads based on alternating currents  other than the main grid supply. The deliberated system consists of a combination solar panel, a step down converter, a battery, a step up converter, an inverter and a transformer. The technique will purvey a 48V DC  supply to cater to the basic DC loads below 1KW  and 220V AC for the other equipment in the households. The buck converter regulates the output of solar panel to constant voltage, which is stored in a battery and boosted to 48 V direct current and also inverted and boosted to 220V AC  as per household requirements. The proposed system will enable the efficacious transmission and distribution of energy by ensuring direct current supply to appliances which are capable of running on the same. This will enhance new possibilities as the need for rectifier within household appliances will be ruled out, thereby reducing their size and cost. The purported idea is an inception to the rampant usage of direct current loads in households and industries.